The Use of Chemicals and Recycled Oil Palm Plantation Production Waste and Impact on Groundwater Quality - Candra, Kalepi; Budianta, D.; A. Napoleon, A. x; Antoni, Mirza (Sriwijaya Journal of Environment, 2024)
The use of wetlands for oil palm plantation is associated with a negative impact on the environment. Meanwhile, oil palm plantation plays a crucial role in supporting the social economy of the community. This study aimed to analyze the productivity of private oil palm plantation in wetlands and the impact on groundwater quality. The experiment was carried out by calculating the amount of production mathematically and taking groundwater samples to be tested in the laboratory. Data were obtained on the amount of PH, BOD, COD, DO, NO3-N, NH3, Cd, Cu, Pb, Zn, CI, and SO42 in groundwater. The results showed an increase in FFB production of up to 42.44%, but there was a change in groundwater quality. Water quality decreased due to an increase in the amount of BOD 312.31%, NO3-N 23.95%, NH3 100%, Cd 166.67%, Cu 433.33%, Pb 200%, Zn 3.800%, Ci 1,672.59%, and SO42 16.19%. Based on the results, it is necessary to increase the amount of compost used while reducing the application of inorganic fertilizers and recycled materials left over from PKS production. Pesticides and herbicides should be used effectively according to standard requirements.